Upaya Meningkatkan Daya Ingat Anak Menghafal Hadits melalui Metode Gerakan - Juliana Juliana (Aṭfāluna: Journal of Islamic Early Childhood Education, 2018)
This research aims to determine the increase in memory of children in memorization of Hadith through movement method in PAUD Darul Fikri. This type of research is classroom action research, which was held in July 2018 until August 2018. The study consisted of two cycles with four main activities present on each cycle, namely planning, observation action, and reflection. Data is analyzed using qualitative data and quantitative data. The subject in this study was a child in the Darul Fikri PAUD. A total of 17 children. The data collection techniques used are oral test and observation techniques. Oral tests include how many hadiths have been memorized and the child's ability to repeat their memorization. While the observation is done directly to see the implementation of the program of memorization of the hadith in Paud Darul Fikri.